2001
DOI: 10.1023/a:1011047829414
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The purpose of this study was to isolate fungi from the quarter milk of cow udders in 9 dairy farms. The samples were collected between May 1996 and April 2000 in the Lublin region. Six hundred and four milk samples collected from the quarters of 172 cows with clinical and subclinical mastitis were examined. Milk samples were plated as soon as possible on blood agar (BA), Mac Conkey agar, aesculin-tallium acetate-crystal violet blood agar, and Sabouraud agar with chloramphenicol and gentamicin. Fifty eight (9.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
10
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(17 citation statements)
references
References 4 publications
2
10
1
Order By: Relevance
“…Krukowski et al [10] isolated fungi as pure cultures from 9.6% of investigated milk samples in the Lublin region in Poland, a result much similar to ours. According to Casia dos Santos and Mo acir Marin [11], the percentage of fungal isolation in surveys carried out in many countries varies considerably, with 6,1% rates described in Egypt [12], 1,3% in Denmark [13], and 12,07% in Brazil [14].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Krukowski et al [10] isolated fungi as pure cultures from 9.6% of investigated milk samples in the Lublin region in Poland, a result much similar to ours. According to Casia dos Santos and Mo acir Marin [11], the percentage of fungal isolation in surveys carried out in many countries varies considerably, with 6,1% rates described in Egypt [12], 1,3% in Denmark [13], and 12,07% in Brazil [14].…”
Section: Discussionsupporting
confidence: 87%
“…Although the distribution of Candida species shows diversity in several countries, it is important to note the increase in number of mammary gland infections caused by Candida species in the recent years. Krukowski et al [10] reported that the most frequently isolated species in Poland were C. kefyr, C. cirferi, and C. krusei. In the other reports, more frequent were C. krusei, C. rugosa, and C. albicans, as described by Costa et al [2, 14, 16] or Şeker [15].…”
Section: Discussionmentioning
confidence: 99%
“…However, the rate of C. krusei isolates of our finding was higher than others. Ruz-Peres et al reported a 18.18% [ 13 ], ErbaŞ et al reported a 17.4% [ 10 ], Ksouri et al reported a 15.57% [ 14 ], Krukowski et al reported a 15.5% [ 15 ], and Eldesouky et al reported a 12.2% of C. krusei isolates in cow mastitis [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Only one reported case of feline otomycosis ( Kano et al , 2000 ). Likewise, its isolation is also rarely reported in other animal species, although it has been found in the neck of swine, bovine placenta ( Furman and Ahearn, 1983 ) and mastitis ( Krukowski et al , 2000 ). However, its role in the pathogenesis of the disease is still unclear.…”
mentioning
confidence: 99%